VARIATIONS IN NUTRIENT AND PHYTOCHEMICAL CONSTITUENTS IN LEAF, STEM AND ROOT OF Garcinia Manni Oliv. DOMESTICATED IN TROPICAL SOIL - Mbosowo, Etukudo; Gift, Fubara (International Journal of Research -GRANTHAALAYAH, 2018)
Variations in nutrient and phytochemical constituents in leaf, stem and root of Garcinia manni (Oliv.) domesticated in tropical soil of Akwa Ibom State were assessed. Plant materials (leaf, stem and root) were collected from three (3) sampling locations in the study area. Elemental nutrient, proximate and phytochemical contents in the leaf, stem and root of G. manni were determined using standard procedures. There were significant (P < 0.05) variations in contents of nutrient elements, proximates and phytochemicals in leaf, stem and root of the test plant. The contents of anti-nutrients (cyanide, phytate, oxalate and glycoside) were relatively lower in stem than those of the leaf and root of the test plant. This study suggests that the test plant parts could be used as valuable material for the production of pharmaceutical drugs. In addition, the lower contents of anti-nutrients in the stem attest to its utilization as chewing stick.